Two new species of the genus Kabakra Dworakowska from Thailand (Hemiptera: Cicadellidae: Typhlocybinae) - Song, Yue-Hua; Li, Zi-Zhong; Dietrich, Christopher H. (Zootaxa, 2016)
The leafhopper genus Kabakra was established with Kabakra augusta from Vietnam as its type species by Dworakowska (1979). Later, another two species were described from India (Sohi & Mann 1992, Mathew & Ramakrishnan 1996). The genus was reviewed by Cao et al. (2012), who redescribed the genus and added three new species from China and Thailand. So far, six species have been reported, all from the Oriental region (see Dmitriev, 2016). In the present paper, two new species, K. chaiyaphuma and K. sakona spp. nov. are described and illustrated, with a key and a checklist to all known species of Kabakra.